Secondary prevention of stroke in atrial fibrillation, use of apixaban: ARISTOTLE, AVERROES studies - V.A. Parfenov (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2014)
Ischemic stroke (IS) prevention in non-valvular atrial fibrillation (NVAF) patients who already had IS or Transient Ischemic Attack (TIA) is the actual problem of up-to-date neurology. The article analyses methods of IS secondary prevention in AF, particularly usage of vitamin Kantagonist – warfarin and new oral anticoagulants: inhibitors of Xa factor (apixaban, rivaroxaban) and direct thrombin inhibiror – dabigatran.Presented results ARISTOTLE study, where have defined preference apixaban vs warfarin, and AVEEROES study, where have shown preference apixaban vs ASA in AF patients. It was noted that apixaban demonstrated superiority vs warfarin in all of the 3 key outcomes:stroke/systemic embolism prevention, including recurrent, major bleeding reducing, reduction in all-cause mortality. Optimization of secondary stroke prevention in AF patients can lead to substantial reduction of morbidity and mortality in our country.